Assessing the factors that influence the donation of a deceased family member's organs in an opt-out system for organ donation. (January 2023) - Shepherd, Lee; O'Carroll, Ronan E.; Ferguson, Eamonn
Abstract: Rationale: Family, and sometimes longstanding friends, have considerable influence over organ donation, through agreeing or disagreeing to the donation of a deceased individual's organs. To date, most research has been undertaken within opt-in systems. Objective: This study advances on previous research by assessing next-of-kin approval under opt-out legislation. We tested whether next-of-kin approval varies when the deceased is a registered donor (opted-in), registered non-donor (opted-out) or has not registered a decision under an opt-out policy (deemed consent). We also tested if the deceased's wishes influenced next-of-kin approval through relatives anticipating regret for not donating and feelings of uncertainty. Finally, we assessed whether next-of-kin's own beliefs about organ donation influenced whether they followed the deceased's wishes. Methods: Participants (N = 848) living in a country with opt-out legislation (Wales, UK) were asked to imagine a relative had died under an opt-out system and decided if their relatives' organs should be donated. Participants were randomly allocated to imagine the deceased had either (i) opted-in, (ii) opted-out or (iii) not registered a decision (deemed consent). The outcome variable was next-of-kin approval, with uncertainty and anticipated regret as potential mediators and next-of-kin's beliefs about organ donation as moderators. Results: Next-of-kin approval was lower when the deceased had opted-out than under deemed consent. This was due to next-of-kin anticipating more regret for not donating under deemed consent than opt-out. Further analyses revealed the deceased's wishes influence next-of-kin approval, via anticipated regret, when next-of-kin did not hold negative beliefs about organ donation. Conclusions: The deceased's wishes were less likely to be followed when next-of-kin had negative beliefs towards donation. Developing large-scale campaigns to improve these beliefs in the general public should make people more likely to follow the deceased's wishes. As a result, these campaigns should improve the availability of donor organs. Highlights: Under opt-out policy, family approval is higher under deemed consent than opt-out. Under opt-out, policy anticipated regret is higher under deemed consent than opt-out. Anticipated regret mediates the effect of deceased's wishes on family approval. Negative donation beliefs weaken the effect of the deceased's wishes on approval.